Pregnant Women’s Anxiety and Depression Symptoms and Influence Factors in the COVID-19 Pandemic in Changzhou, China - Wang, Li; Yang, Ni; Zhou, Hua; Mao, Xueqin; Zhou, Ying (Frontiers in Psychology, 2022)
Background: With the coronavirus disease 2019 pandemic (COVID-19), pregnant women’s psychological conditions have become a global challenge. The aim of the study was to identify the prevalence of anxiety and depression symptoms and analyze their influence factors among pregnant women in Changzhou, China during the COVID-19 pandemic and provide them with appropriate health-care strategies. Methods: Participants were 681 pregnant women who visited various obstetric and gynecology clinics in Changzhou, China between 25 February and 7 March 2020. They were asked to complete an online survey. The Generalized Anxiety Disorder Scale-7 (GAD-7) and Patient Health Questionnaire-9 (PHQ-9) were used to detect anxious and depressive symptoms. The chi-squared test and multivariate logistic regression analysis were carried out to examine the associated factors in these groups. Results: Overall, the prevalence of anxiety and depression symptoms among pregnant women were 31.72% and 36.12%, respectively, but most of them were mild. Having an irregular diet with poor subjective sleep quality, perceiving little family support, spending too much time on news related to the coronavirus, and having severe subjective life impact by the coronavirus were related to anxiety and depression symptoms. In addition, lack of physical exercise and exposure to electronic screens over 5 hours per day were associated with depression symptoms. Conclusion: Pregnant women with an irregular diet, poor sleep quality, little family support, excessive attention to COVID-19 news, and life impacted by the coronavirus severely are at high risk for anxiety and depression symptoms during the COVID-19 pandemic. This indicates that targeted measures to address mental health in pregnant women during the pandemic period are needed.